Nursing Professionals within the Intergenerational Context during the 20th and 21st Centuries: an Integrative Review - Susana Rollan Oliveira (Universidad de Antioquia, 2021)
Objective. To describe the generational differences and similarities existing among nursing professionals of the 20th and 21st centuries and how these have influenced on the evolution of the profession.